Localized application of insecticide combined with fertilizer on corn controls Spodoptera frugiperda (smith) and reduces spray drift - Campos, H. B.N. [UNESP]; Ferreira, M. C. [UNESP]; Costa, L. L. [UNESP]; Decaro Júnior, S. T. [UNESP]; Lasmar, O. [UNESP] (Science Alert, 2014)
Pesticides are important tools in agriculture for several decades, providing control of pest and diseases for an increasing demand of food by the growth of population. However, pesticides are often associated with contamination, both in food and environment. A change in application method makes spraying more safe and viable but the development of new techniques is a challenge. This study describes the evaluation of different strategies of insecticide application in the control of Spodoptera frugiperda (Smith) on corn. Techniques of insecticide application (localized application combined with nitrogenous (N) fertilizer and total area application); models of spray nozzles (pre-orifice and air induction) at different angles, flow rates, pressures and spray volumes (50, 100 and 150 L ha-1) were evaluated on the fall armyworm control. The localized application combined with fertilizer were found possible, controls fall armyworm and reduces the amount of off-target insecticide exposure in total treated area. Appropriate techniques for the chemical control of S. frugiperda have been discussed. This new technique enables two operations within a single pass of the tractor and suggests a simple and low-cost installation that can be readily adopted by small family farms.
Keywords: Application technology; Family farms; Spray nozzles; Spray volumes; Zea mays